THE ANALYSIS OF SEMANTIC AND PRAGMATIC CONTEXT IN TOEFL TEST SIMULATION ON LISTENING SECTION - Rakha Setyawan; Triastama Wiraatmaja (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2018)
Sociolinguistics aspects such as Semantic and Pragmatic affect language user in every situation. Those two contexts even exist in a proficiency test to become the test foundation. This research was conducted to identify the semantic and pragmatic contexts in TOEFL test simulation on the Listening section. The researcher applied a qualitative descriptive approach to this research, and Document Analysis and the researcher as the instrument. The object of this research was TOP NO 1 TOEFL SIMULATION published by FORUM TENTOR INDONESIA. The result reveals that there are several types of semantic and pragmatic context found in the test simulation. The semantic contexts found in 8 questions from the 30 questions analyzed. The types of semantic contexts which were found namely; Meaning, Semantic Feature, and Semantic Roles. Moreover, the semantic type that mostly occurred is Semantic Roles (4 Questions), then followed by Semantic Feature (2 Questions) and Meaning (2 Questions). However, the Pragmatic context quantities are found more than the semantic context. From the 30 analyzed questions, the Pragmatic contexts found are 40 questions, it happens because one test item can have more than one type of pragmatic. Also, the Reference type in Pragmatic occurred in most questions because the narrator on the listening passage uses referencing (nature of Reference) to make the question. The type of pragmatic context found namely; Context, Politeness, Reference, and Speech Act. The type of pragmatic context which is mostly occurred is Reference (25 questions).